Tutorial: Road Lighting for Efficient and Safe Traffic Environments. Issue 4 (2nd October 2017) - Tetri, Eino; Bozorg Chenani, Sanaz; Räsänen, Rami-Samuli; Baumgartner, Hans; Vaaja, Matti; Sierla, Seppo; Tähkämö, Leena; Virtanen, Juho-Pekka; Kurkela, Matti; Ikonen, Erkki; Halonen, Liisa; Hyyppä, Hannu; et al.
ABSTRACT: This article discusses various aspects of outdoor lighting energy efficiency by means of new light sources and smart lighting systems. We will also discuss visibility, traffic flow, safety, and environmental and economic aspects. The use of an optimum level of road lighting maximizes the contrast between the background and the object to be seen. This suggests that the combined effect of road lighting and car headlights should be taken into account. Solutions for future measurement need to include 3D modeling of the lighting environment and mesopic photometry. The life cycle environmental impacts of high-pressure sodium (HPS) and light emitting diode (LED) luminaires were found to be on a similar level, but it is expected that LED luminaires will surpass HPS luminaires in environmental friendliness across the whole life cycle in the future. The energy-saving potential is based on new energy-efficient technology, reduced burning hours with smart control, and new lighting dimensioning. The energy saving potential when replacing HPS lamps with LED luminaires is 31% with current technology and 66% with improved technology in the future. Further energy savings are achievable with reduced burning hours enabled with smart lighting. Altogether, the energy-saving potential of the future LED luminaire is 83% compared to current HPS luminaires.